Bettors Love Skewness, Not Risk, at the Horse Track - Golec, Joseph; Tamarkin, Maurry (Journal of Political Economy, 1998)
Studies of horse race betting have empirically established a long shot anomaly; that is, low‐probabiliy, high‐variance bets (long shots) provide low mean returns and high‐probability, lowvariance bets provide relatively high mean returns. Because bettors willingly accept low‐return, high‐variance bets, researchers conclude that bettors are risk lovers. In this study, we show that the data are at least as consistent with risk aversion as they are with risk loving when one explicitly considers the skewness of bet returns. Because the variance and skewness of bet returns are highly correlated, bettors may appear to prefer variance when it is skewness that they crave.